Reticulate Acropigmentation Of Kitamura - Srikanth; Mohan Thappe Devinder; Ratnakar Chaganti (Wolters Kluwer Medknow Publications, 1999)
A 42 year old male patient having reticulate acropigmentation of Kitamura is being reported for the first time from South India.